Independent Learning for Improving English Skills of Students in English Language Education, Pekalongan University - Dwi Ario Fajar; Dwi Agustina (Faculty of Language and Literature, University of Surakarta, 2019)
This research reports the findings of a narrative inquiry aiming at revealing the lecturers' perceptions about the meaning and importance of independent learning for improving students' mastery of English. This research involved nine lecturers of English Education program at the Faculty of Teachers’ Training and Education, Pekalongan University. The lecturers were interviewed about their views of independent learning. The findings suggest that all of the respondents agreed on the importance of independent learning. However, in terms of the meaning of independent learning, the lecturers suggest a various definition of independent learning, signaling that their understanding on the concept of independent learning is not similar which may result in different practices of giving independent learning tasks to students.